Oral Cancer Knowledge and Awareness in Patients Visiting Kantipur Dental College - Bajracharya, Dipshikha; Gupta, Sujaya; Sapkota, Manish; Bhatta, Shishir (Journal of Nepal Health Research Council, 2018)
Background: Lack of knowledge and awareness about oral cancer, its risk factors and negligence of the early warning signs play crucial role in raising the incidence of the disease. The present study was carried out to evaluate the awareness of oral cancer among patients visiting Kantipur Dental College, Kathmandu, Nepal.Methods: The cross-sectional study was done in 471 patients from 15-85 years. Self administered questionnaire was prepared which comprised of knowledge of oral cancer, source of information, its early signs and symptoms along with the awareness of its risk factors.Results: Most of the participants (41.80%) had not heard of oral cancer. 31.60% recognized tobacco smoking and tobacco chewing as the chief risk factor with 15.50% and 10.80% of participants who identified white patch and red patch as early sign of oral cancer respectively. Pearson’s chi square test was used which showed statistically significant association of total mean knowledge score and awareness score with age, education level and occupation (p